Management of Adrenal Masses in Children and Adults - Kebebew, Electron (Springer International Publishing : Imprint: Springer, 2017)
This book is designed to present a comprehensive and state-of the-art approach to the management of adrenal neoplasms that provides a resource to the broad group of providers that will encounter such a patient. Sections address issues that are faced by providers who encounter a patient with an adrenal neoplasm. These areas include an overview of the genetic basis and familial cancer syndrome-associated with adrenal neoplasms, pathobiology, advanced and tumor specific imaging approaches and technologies, biochemical analysis, standard medical and surgical therapies, and emerging technology and treatment approaches to benign and malignant adrenal neoplasms. Written by experts in the field, each of these sections address level of clinical evidence and provide recommendations and treatment algorithms. Extensive illustrations make this an interactive text. Management of Adrenal Masses in Children and Adults will serve as a very useful resource for all providers dealing with, and interested in this common but challenging tumor. It will provide a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts.